EDUKASI KEBUTUHAN VITAMIN D DARI SINAR MATAHARI UNTUK PENCEGAHAN COVID-19 PADA KOMUNITAS PEREMPUAN HIJAB KELOMPOK IBU-IBU PENGAJIAN DI MASJID AL MANSHUURIN YABANSAI HERAM KOTA JAYAPURA, PAPUA - Herlambang Budi Mulyono; Trajanus Laurens Yembise; Dais Iswanto (LPPM Uncen, 2023)
The service was carried out on Saturday, 13, August 2022 virtually by zoom. The participants present consisted of several differences in ethnic background, educational work and age. The results with devotion show good participant satisfaction, it is characterized by some questions from an excellent audience regarding the topic of devotion. The service material consists of the topics of Vitamin D, Covid-19 and the relationship between the two. The Covid-19 material includes a brief history, characteristics of the Covid-19 virus, signs of infection, common symptoms, how to prevent and how to wash the hands with 6 steps correctly. After that, it was continued with an exposure between the role of Vitamin D and Covid-19 infection which consisted of an explanation of the general molecular mechanism and some recent studies on covid-19 and vitamin D. activities in general went smoothly and according to the activity plan.Keywords: covid-19; vitamin D; hijab woman; infection